Crtc1 deficiency protects against sepsis-associated acute lung injury through activating akt signaling pathway - Meng Chen; Jian Lv; Ningning Guo; Tuo Ji; Yu Fang; Zhihua Wang; Xianghu He (BMC, 2024)
Abstract Background Interplay between systemic inflammation and programmed cell death contributes to the pathogenesis of acute lung injury (ALI). cAMP-regulated transcriptional coactivator 1 (CRTC1) has been involved in the normal function of the pulmonary system, but its role in ALI remains unclear. Methods and results We generated a Crtc1 knockout (KO; Crtc1 −/−) mouse line. Sepsis-induced ALI was established by cecal ligation and puncture (CLP) for 24 h. The data showed that Ctrc1 KO substantially ameliorated CLP-induced ALI phenotypes, including improved lung structure destruction, reduced pulmonary vascular permeability, diminished levels of proinflammatory cytokines and chemokines, compared with the wildtype mice. Consistently, in lipopolysaccharide (LPS)-treated RAW264.7 cells, Crtc1 knockdown significantly inhibited the expression of inflammatory effectors, including TNF-α, IL-1β, IL-6 and CXCL1, whereas their expressions were significantly enhanced by Crtc1 overexpression. Moreover, both Crtc1 KO in mice and its knockdown in RAW264.7 cells dramatically reduced TUNEL-positive cells and the expression of pro-apoptotic proteins. In contrast, Crtc1 overexpression led to an increase in the pro-apoptotic proteins and LPS-induced TUNEL-positive cells. Mechanically, we found that the phosphorylation of Akt was significantly enhanced by Crtc1 knockout or knockdown, but suppressed by Crtc1 overexpression. Administration of Triciribine, an Akt inhibitor, substantially blocked the protection of Crtc1 knockdown on LPS-induced inflammation and cell death in RAW264.7 cells. Conclusions Our study demonstrates that CRTC1 contribute to the pathological processes of inflammation and apoptosis in sepsis-induced ALI, and provides mechanistic insights into the molecular function of CRTC1 in the lung. Targeting CRTC1 would be a promising strategy to treat sepsis-induced ALI in clinic.